(untitled) (Italiano LinguaDue, 2021)
Questo studio contrastivo analizza il lessico medico in italiano e in tedesco da un punto di vista teorico-sistematico e didattico. Esistono due tipi di tecnicismi: i tecnicismi specifici, per lo più formazioni neoclassiche con elementi greco-latini (chiamate anche internazionalismi) e i cosiddetti tecnicismi collaterali che hanno la mera funzione stilistica di innalzare il registro. Il presente articolo tratta il lessico medico nella prospettiva dell’insegnamento della traduzione specializzata a parlanti madrelingua tedeschi. The lexicon of medicine. An Italian-German comparison from a didactic-translating perspective In this contrastive study, medical vocabulary in Italian and German is analyzed from a systemic and didactic point of view. There are mainly two types of technical terms: proper terms, mostly neoclassical formations made up of Latin or Ancient Greek elements (also called internationalisms), and “collateral” terms which have only a stylistic function. This article deals with medical vocabulary from the perspective of teaching specialized translation to German native speakers.